Nesiller Arası Adalet ve Ekonomik Krizler - DEMİRCİ, SERVER (My University, 2015)
0

The crisis that occurred in the US after 2007 was a financial crisis. The cause of the crisis was the mortgage-backed securities market. As in every crisis episode, economist tried to model that crisis as well and analysed the reasons behind. Only a handful of them have been able to predict the crisis. As in every crisis, the models did not include the human factor and human behaviour but some mathematical explanations. This study focuses on the shortcomings of such approach.
Intergenerational Justice and Economic Crisis
Keywords: Hukuk